Using the Mouse Grimace Scale to Reevaluate the Efficacy of Postoperative Analgesics in Laboratory Mice - Matsumiya, Lynn C (American Association for Laboratory Animal Science, 2012)
Postoperative pain management in animals is complicated greatly by the inability to recognize pain. As a result, the choice of analgesics and their doses has been based on extrapolation from greatly differing pain models or the use of measures with unclear relevance to pain. We recently developed the Mouse Grimace Scale (MGS), a facial-expression–based pain coding system adapted directly from scales used in nonverbal human populations. The MGS has shown to be a reliable, highly accurate measure of spontaneous pain of moderate duration, and therefore is particularly useful in the quantification of postoperative pain. In the present study, we quantified the relative intensity and duration of postoperative pain after a sham ventral ovariectomy (laparotomy) in outbred mice. In addition, we compiled dose–response data for 4 commonly used analgesics: buprenorphine, carprofen, ketoprofen, and acetaminophen. We found that postoperative pain in mice, as defined by facial grimacing, lasts for 36 to 48 h, and appears to show relative exacerbation during the early dark (active) photophase. We find that buprenorphine was highly effective in inhibiting postoperative pain-induced facial grimacing in mice at doses equal to or lower than current recommendations, that carprofen and ketoprofen are effective only at doses markedly higher than those currently recommended, and that acetaminophen was ineffective at any dose used. We suggest the revision of practices for postoperative pain management in mice in light of these findings.